Cardiovascular adverse events induced by immune checkpoint inhibitors: A real world study from 2018 to 2022 - Wu, Si; Bai, Hansheng; Zhang, Ling; He, Jiamin; Luo, Xiangru; Wang, Shiyi; Fan, Guangjun; Sun, Na (Frontiers in Cardiovascular Medicine, 2022)
Background The reported rate of cardiovascular adverse events (CAE) caused by immune checkpoint inhibitors (ICI) is low but potentially fatal. Assess the risk of CAE in cancer patients and compare the incidence of CAE between Chinese developed ICIs and imported ICIs. Methods A retrospective analysis was performed on cancer patients treated with ICI for at least four cycles in the Second Affiliated Hospital of Dalian Medical University from January 2018 to March 2022. Baseline characteristics, physiological and biochemical values, electrocardiographic and echocardiographic findings were compared between patients with and without CAE. Results Among 495 patients treated with ICIs, CAEs occurred in 64 patients (12.93%). The median time to the event was 105 days (61–202). The patients with low neutrophil-to-lymphocyte ratio (L-NLR) were significantly associated with the risk of developing CAE (hazard ratio HR 3.64, 95% confidence ratio CI 1.86–7.15, P = 0.000). Patients with higher comorbidity burden significantly increased the risk of developing CAE (HR 1.30, 95% CI 1.05–1.61, P = 0.014). Those who received a combination of ICI and vascular endothelial growth factor receptor (VEGFR) inhibitors (HR 2.57, 95% CI 1.37–4.84, P = 0.003) or thoracic radiation therapy (HR 32.93, 95% CI 8.81–123.14, P = 0.000) were at a significantly increased risk of developing CAE. Compared to baseline values, creatine kinase is -oenzymes (CK-MB) (95% CI -9.73 to -2.20, P = 0.003) and cardiac troponin I (cTnI) (95% CI -1.06 to -0.06, P = 0.028) were elevated, and the QTc interval prolonged (95% CI -27.07 to -6.49, P = 0.002). Using nivolumab as a control, there was no difference in CAE risk among the eight ICIs investigated. However, the results of the propensity matching showed that programmed death-ligand 1 (PD-L1) inhibitors had lower CAE occurrence compared with programmed cell death protein 1 (PD-1) inhibitors (adjusted HR = 0.38, P = 0.045). Conclusion Patients who received concurrent VEGFR inhibitors and ICIs had a history of thoracic radiation therapy, L-NLR, and higher comorbidity burden had an increased risk of CAEs. Elevated cTnI, CK-MB, and QTc, can be used to monitor CAEs. There was no significant difference in CAE risks between Chinese domestic and imported ICIs. PD-L1 inhibitors had lower CAE occurrence than PD-1 inhibitors.